Indoor Radon Activity Concentration Survey of Family Houses in Pest County - Fekti, László Richard; Székely, László; Horváth, Márk; Géczi, Gábor (Journal of Central European Green Innovation, 2022)
Thanks to the measures taken to prevent the coronavirus epidemic, we have spent more time indoors than before, for example in our homes. It is not only the airborne Covid-19 virus that affects our bodies, but also ionizing radiation from natural sources, higher carbon dioxide concentrations from the breathing of those staying indoors, or pollutants entering the air from our activities (cooking, smoking, etc.). In addition to the way of life of the residents, the structure of the buildings, the built-in boundary structures and the building engineering units (thermal energy production, ventilation) determine the quality of the indoor air.In December 2019, we started a series of measurements aimed at determining the indoor radon concentration in the eastern part of Pest County, involving 24 family houses in 7 settlements. Our results clearly show the difference between the seasons, but differences can also be found between the architectural and building engineering solutions of the family houses.
Keywords: indoor; pollutant; radon; ventilation; air quality